Economic Intervention and Parenting: A Randomized Experiment of Statewide Child Development Accounts. (July 2016) - Nam, Yunju; Wikoff, Nora; Sherraden, Michael
Objective: We examine the effects of Child Development Accounts (CDAs) on parenting stress and practices. Methods: We use data from the SEED for Oklahoma Kids (SEED OK) experiment. SEED OK selected caregivers of infants from Oklahoma birth certificates using a probability sampling method, randomly assigned caregivers to the treatment ( n = 1, 132) or control group ( n = 1, 098), and provided college savings incentives only to the treatment group. We run regression analyses on a parenting stress scale and six continuous measures of parenting practices. Results: There were no significant differences in parenting outcomes between treatment and control groups, with the exception of frequency of screaming at the child. CDAs have more salient effects on American Indians than on other groups. Conclusions: We present weak evidence for CDAs' positive impacts on parenting outcomes. Further research is needed to determine whether these initial results change over time.